2022
DOI: 10.1001/jamaoncol.2022.1638
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion and Reporting of Transgender and Nonbinary Persons in Clinical Trials and Tumor Registries—The Time Is Now

Abstract: This Viewpoint advocates for the inclusion of transgender and nonbinary persons in clinical trials and tumor registries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…In addition, the gay, bisexual, lesbian, transgender, and intersex populations also need more attention from future trials 94,95 . As the transgender population increases, 96 the implications that gender‐affirming hormone therapy and social determinants of health may have on immunotherapy effectiveness should be better evaluated 94–97 . Moreover, since sexual chromosomes can have several roles in immune response and regulation, 93 intersex patients should also receive more attention based on their chromosome status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the gay, bisexual, lesbian, transgender, and intersex populations also need more attention from future trials 94,95 . As the transgender population increases, 96 the implications that gender‐affirming hormone therapy and social determinants of health may have on immunotherapy effectiveness should be better evaluated 94–97 . Moreover, since sexual chromosomes can have several roles in immune response and regulation, 93 intersex patients should also receive more attention based on their chromosome status.…”
Section: Discussionmentioning
confidence: 99%
“… 94 , 95 As the transgender population increases, 96 the implications that gender‐affirming hormone therapy and social determinants of health may have on immunotherapy effectiveness should be better evaluated. 94 , 95 , 96 , 97 Moreover, since sexual chromosomes can have several roles in immune response and regulation, 93 intersex patients should also receive more attention based on their chromosome status. Consequently, upcoming studies and clinical trials should consider addressing these questions in their designs to guarantee a better‐personalized approach for the future.…”
Section: Discussionmentioning
confidence: 99%
“…Because transgender individuals experience incongruence between the sex assigned to them at birth and their sex identity, they are excluded from conventional clinical studies (or standard screening) that require persons to identify within the typical sex dichotomy criteria (male or female) (Cortina, 2022). There are no studies that have evaluated routine screening mammography for transgender women (MtF) upon treatment with hormonal therapy; however, recent cohort studies have reported multiple cases of BC in these populations.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of gender-affirming operations for transmasculine persons include chest masculinization surgery, colloquially called top surgery, in which the majority of breast tissue is removed, and bottom surgery, which includes metoidioplasty, phalloplasty, and scrotoplasty and may also include hysterectomy with or without bilateral-salpingo oophorectomy . While gender-affirming therapies are used to treat gender incongruence and/or gender dysphoria and are associated with improved mental health outcomes and overall well-being for transgender and nonbinary individuals, the potential long-term effects that these therapies may have on overall health, particularly gender-affirming hormone therapy and the risk of hormonally sensitive malignant tumors, is not currently well understood …”
mentioning
confidence: 99%
“…Although it will take time and continued research to elucidate the potential long-term effects of gender-affirming therapies, surgeons who perform gender-affirming operations can currently minimize the risk of future cancer development by considering germline genetic testing prior to gender-affirming surgeries for individuals who may harbor a germline genetic sequence variant or are at increased cancer risk based on family history alone. Pathogenic germline variants known to cause hereditary breast and ovarian cancer syndromes, most notably the BRCA1 and BRCA2 sequence variants, can significantly influence the type of gender-affirming operations that transgender and nonbinary persons may choose to undergo.…”
mentioning
confidence: 99%